Flow interference between groups of three and four equispaced cylinders - Sayers, A T (Department of Mechanical Engineering, 2016)
This thesis is a study of the interference forces acting on one cylinder comprising a group of three and four cylinders when situated in a free stream flow. The spacing of the cylinders was such that the lines joining their axes formed an equilateral triangle, and a square respectively. The study is split into two parts, (a) potential flow over the groups of cylinders (b) real flow over the groups of cylinders. Bound with copies of the authors' published papers.~Bibliography: pages 132-137.